KILAS BALIK KEBIJAKAN WAJIB BELAJAR DAN INPRES PADA MASA ORDE BARU - Nababan, Celynta Salonica; Delvi, Latika; Pratiwi, Yessi Nanda (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research discusses one of President Soeharto's educational policies in the field of education, namely the compulsory education program. This compulsory education program ultimately sparked Suharto's idea of building elementary schools and repairing damaged school buildings which were then called Presidential Instruction Elementary Schools (SD Inpres). The aim of this research is to examine what problems occur in the Compulsory Education policy and the construction of SD Inpres. The method used in this research is the historical method which includes heuristics, verification, interpretation and historiography. The research results show that the compulsory education program in the era of President Soeharto has not fully achieved the expected goals. This is because many people are not aware of the importance of education, there is misappropriation of funds by certain parties, the educational gap that occurs in society is still very visible, and the development carried out is only aimed at political interests. The construction of SD Inpres only prioritizes quantity without paying attention to quality developments. At this time, the most important thing is to create as many educated graduates as possible without looking at the quality of teaching and educational outcomes